The Warship Hazardous Prize – Site Investigations 1992–2022 - Pascoe, Daniel (The international journal of nautical archaeology, 2024)
In shallow water off the coast of West Sussex in England lies the wreck of a French built, English warship, lost in 1706. The remains represent a hybrid of French construction and armament with English organisation and adaption. This paper brings the site’s investigations up to date, discussing new records relating to the structure and internal layout of the main site, as well as the discovery of several new areas, rich in guns and other artefacts.